Methodological preparation of students for spiritual activity by studying the topic "Solar system, Planets" using interactive methods - Shodiyev N; Nabiyeva D., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, in the process of education, the scientific heritage of scholars and thinkers of Movaraunnahr and the achievements of our science in this field will be absorbed into the educational content dedicated.